KOMBINASI METODE SAP, STUDI KASUS, SIMULASI KONDISI SEBAGAI INOVASI PROGRAM PELATIHAN UNTUK MENINGKATKAN KINERJA SDM DI BANK BAPAS 69 MAGELANG - Natriyani, Sholikah; Siharis, Alkadri Kusalendra (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
The goal is to describe human resources training conducted in PD. BPR BANK BAPAS 69 Magelang. In this study the writers employed the qualitative method of applying data collection techniques by observation and interview. The determined source used in this study is an overwhelmingly sampling technique. The branch head, the cashier, customer service, credit analysis or banking staff that are the informants in the study. In this study writers used triangulation techniques to test data's accuracy and validity.The results showed that the method used was less effective, where the training process for employees used the seminar method and little practice. The author proposes innovations in HR training methods that can be applied by PD. BPR Bank Bapas 69 Magelang to support the effectiveness of the training program being held. The program innovation that can be proposed by the author is the implementation of SAP Success Factors Continuous Performance Management (CPM) which is software on gadgets managed by HR to facilitate the provision of guidance and coaching for employees and coaches combined with programs, namely solving case studies and simulation of work-related conditions. It is hoped that this will provide better outcomes in increasing the productivity and performance of human resources than just a colloquy.